QUALITY OF LIFE IN ADULTS WITH INTELLECTUAL DISABILITIES – OBJECTIVE INDICATORS - Kaljača, Svetlana; Dučić, Bojan; Đorđić, Sara (Specijalna edukacija i rehabilitacija, 2018)
The aims of this research were to determine the level of objective Quality of Life (QoL) in adults with intellectual disabilities (ID), the difference in QoL with regard to the participants’ gender, as well as the relation among the examined life domains included in the applied QoL concept. The sample included 39 adults with mild and moderate ID aged between 22 and 50 (M=34.69, SD=7.49), and 40 typically developing (TD) participants between 19 and 60 years of age (M=35.25, SD=12.21). Seven domains of Comprehensive Quality of Life Scale – ID: Material well-being, Health, Productivity, Intimacy, Safety, Place in community and Emotional well-being were used to assess QoL level. These domains represent the indicators of objective QoL. Participants with ID had significantly lower QoL than TD participants in the total score (p=0.000) and in Health (p=0.000), Productivity (p=0.000) and Intimacy (p=0.008) domains. When compared to male participants with ID, TD men had a higher total score (p=0.001), and better results in Health (p=0.021) and Productivity (p=0.000) domains. This result was also confirmed in female participants with the addition of TD women being significantly more successful in Intimacy (p=0.027) domain compared to women with ID. Statistically significant correlations among seven domains of QoL objective indictors in persons with ID were positive, ranging from moderate to high. The obtained results indicate the domains which require more intensive support so that people with ID could have the opportunity to achieve QoL which meets the standards of the community they belong to. Key words: Quality of Life, intellectual disabilities, support services, health, productivity, intimacy